Cold case: the forensic economics of energy efficiency labels for domestic refrigeration appliances - Goeschl, Timo (Energy economics, 2019)
Energy-efficiency labels are intended to better inform consumers at the point of sale about unobservable product characteristics. The EU Energy Label is globally one of the largest labeling schemes and obligates manufacturers of white goods to self-certify the energy efficiency index (EEI) of their product. The integrity of the scheme is reliant on manufacturers' compliance with the certification protocol and accurate declaration of the certification results. I construct a database that contains the testing data of 212 refrigeration devices sold on EU markets before and after the introduction of the label and compare self-reported and third-party verified EEIs. I find that under the label (1) there is evidence for bunching in self-certified EEIs, but not in verified EEIs, pointing to misreporting; (2) for the average model, self-certified EEIs understate equivalent energy consumption by 13 to %; (3) understatement clusters at class boundaries; and (4) well over half of the reporting discrepancy can be attributed to systematic factors rather than error. This can explain a significant share of the so-called 'Energy Efficiency Gap.' Before the introduction of the label, there is no evidence for bunching and substantially less underreporting of energy efficiency performance. In its current implementation, the EU Energy Label therefore plausibly induces misreporting, partly negating the intended information gains and impacting negatively on information-attentive consumers.